Intralingual Understanding of Zakat, Infaq, alms, and Gifts in Islamic Economics In Aceh - Najihatul Faridy; Allif Syahputra Bania; Raida Fuadi (PT. Anagata Sembagi Education, 2024)
The implementation of Islamic economics in Aceh has a positive impact on society. Aceh Province is a region in Indonesia that has an influence on poverty issues because it has been hit by social conflict that has been going on for a very long time so that access to work is not conducive for the people of Aceh. ). Aceh Province with the implementation of Islamic law has a role to play in resolving and minimizing poverty problems. The method used by Aceh Province is to foster the management of zakat, infaq and alms because they are sources of eternal funds. Supporting the importance of previous research on zakat, infaq and alms, this study wants to determine the ability to understand interlingual terminology about zakat, alms and infaq plus one other terminology, namely gifts. This research was a descriptive-qualitative research. The data used are 4 terminologies in Islamic economics, namely alms, zakat, infaq and gifts to be translated interlingually. The four terms to be translated were analyzed using the intralingual equivalence method. The sample is 50 students from the Faculty of Economics who have studied science related to Islamic economics courses. The findings obtained that related to the terminology of zakat, all participants as many as 50 students or 100% of participants managed to answer intralingually. Then, there were the same results between the terminology of infak, sedekah, and hadiah, namely 47 students managed to answer correctly but insignificantly there were only 3 students who answered incorrectly.